Pengembangan LKPD IPA Berorientasi Keterampilan Proses Sains Materi Gaya untuk Meningkatkan Pengetahuan Faktual dan Konseptual Kelas IV SD - Budi Andriyani, Novia; Widi Winarni, Endang; Juarsa, Osa (Jurnal Kajian Pendidikan Dasar, 2025)
This research and development study aims to produce a science student worksheet oriented toward science process skills that is valid, practical, and effective in improving elementary students' factual and conceptual knowledge. Existing worksheets did not incorporate science process skill indicators, resulting in students lacking training in essential scientific skills. The study utilized the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through observations, interviews, questionnaires, and tests (pre-tests and post-tests) to assess students’ understanding. Data analysis involved calculating percentages and value ranges at both classical and individual levels. The research subjects were fourth-grade students from two elementary schools. A limited trial was conducted at SD Negeri 2 Sumber Makmur, while effectiveness testing took place at SD Negeri Nibung. The results showed that the implementation of the science process skills-oriented LKPD was effective in enhancing students' factual and conceptual knowledge. This effectiveness is evidenced by an N-Gain score of 0.7288 (high category) for factual knowledge and 0.693 (moderate category) for conceptual knowledge. Based on these findings, it is recommended that teachers adopt science process skill-oriented worksheets to actively involve students in learning activities and promote better understanding of scientific concepts and facts.